Transfering of Meaning in the Modern Uzbek Poetry: Metaphors and Synecdoche - Rajabov, To’xtamurod (FILOLOGIYA UFQLARI JURNALI, 2024)
Metaphor is actually one of the common types of meaning migration in the artistic literature, something is a kind of migration, based on the similarity between phenomena. The meaning of the metaphor in the artistic text is extremely vivid, because it, together with other words that have entered into a relationship, forms a meaningful whole, thanks to the concepts that are formed in contact with them, can be attributed to the width of the meaning. And the scale of artistic metaphor is much wider than the meaning of the term it acts as a context kengaytiradi and estetitk in the influence of the meanings of other words in the text. In the process of studying the types of transportations, we will directly encounter the method of synecdoche, since the method of synecdoche covers all types of transportations by its side. In general, as we have seen above, synecdoche is also based on a meaningful connectionadorlik. If the connection between the lines of meaning is interrupted, then the word moving in meaning becomes a simple lexical concept. Brief first conclusions about the archipelago synecdoche, whose name has not yet been worked anywhere, attract us to understand the poetry of the past and today. The construction and structure of the archipelago synechia is formed by a specific fund of “States of plot and plot”, from which they move from the poem to the poem, from the period to the period.